2021
DOI: 10.3390/biomedicines10010045
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell Distribution Width and Mortality in Patients Undergoing Percutaneous Coronary Intervention

Abstract: Red cell distribution width (RDW) can effectively predict prognosis in coronary artery disease (CAD) patients following percutaneous coronary intervention (PCI). There is currently no relevant research to demonstrate a linear or non-linear association between RDW and mortality. This is a multi-center, retrospective cohort study, with data collected from 2006 to 2017. Source data included electronic medical records of the Integrated Medical Database of National Taiwan University Hospital, and health insurance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Many mechanisms can affect RDW levels, such as in ammatory stress, adrenergic activation, nutritional de ciency and iron homeostasis disorder. Previous studies showed that increased RDW is a powerful independent predictor of cardiovascular events in heart disease patients 23,24 .…”
Section: Discussionmentioning
confidence: 96%
“…Many mechanisms can affect RDW levels, such as in ammatory stress, adrenergic activation, nutritional de ciency and iron homeostasis disorder. Previous studies showed that increased RDW is a powerful independent predictor of cardiovascular events in heart disease patients 23,24 .…”
Section: Discussionmentioning
confidence: 96%
“…Fatemi et al [ 16 ] found that RDW was related to 1-year mortality in patients underwent PCI (HR 1.65, CI 1.22–2.23, P = .001). Liao et al [ 17 ] analyzed the association between RDW and 1-year all-cause and cardiovascular mortalities in patients undergoing PCI, stratified RDW values into 5 groups (13.4%, 14.1%, 14.8%, and 15.9%), and reported that RDW was an independent predicting factor in patients. Furthermore, Xiao et al [ 18 ] conducted a retrospective cohort study investigating the association between change of RDW values defined as ΔRDW with MACE in patients undergoing PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Taiwanese scholars analyzed the RDW level and postoperative mortality of CAD patients undergoing PCI treatment in 2021, and they suggested that RDW may be used to predict the future mortality and prognosis of CAD patients. 32 Although PCI significantly reduced the mortality of ACS, patients after revascularization remain at risk for developing MACEs, which is even more common in patients with DM. Therefore, it is meaningful to analyze the relationship between RDW and FBG and determine the relationship between RDW and MACEs in ACS patients with different FBG levels.…”
Section: Discussionmentioning
confidence: 99%